Legal Respect for Children from Sirri's Marriage in the Perspective of Islamic Marriage Law and Regulations Indonesian Law in the District Labuhanbatu - Khairani Amalia Tambunan; Sriono Sriono; Risdalina Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Sirri marriage is a marriage that is legal according to the viewpoint of the Islamic religion, while a legal marriage according to the provisions of Articles 1 and 2 of the Marriage Law is that apart from being carried out on the basis of religion it must also be registered. This study aims to determine the legal consequences for children resulting from unregistered marriages based on Islamic law and statutory regulations. This study uses an empirical juridical method, which is conducting field research, in order to support data related to this research by conducting research at the Religious Courts.. The results showed that Labuhanbatu Regency is an area where many people still carry out unregistered marriages or sirri marriages. This can be seen from the data from the Rantauprapat Religious Court from 2018 until now, there have been 53 recorded cases regarding under-handed marriages that have been ordained. So that the legal consequence of the child resulting from a Sirri marriage has the status of an out-of-wedlock child and he cannot accept the rights of the child as a child from a legal marriage based on the marriage law. In the life of the nation and state, all citizens are obliged to obey and be bound by the prevailing laws and regulations in Indonesia.